EVALUASI SISTEM INFORMASI AKADEMIK DI JURUSAN KESEHATAN MASYARAKAT FIKES UNSOED - nurhayati, siti; Sistiarani, Colti; Suratman, Suratman (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2017)
Utilization of information technology at this time is one alternative to support the effectiveness and efficiency of performance for an organization. Globalization of the world of education requires universities to be able to manage information well, so that the information needs of each interested party can be met quickly and precisely. One of the information systems that exist in the college is the academic information system. Universities are required to build an academic information system (SIA) that integrates from all academic activities, and provides useful information for stakeholders. In management and planning it is imperative that evaluation is a milestone of a development. This study aims to find out the evaluation of academic information system at FIKES UNSOED based on performance / performance, information / data, economy, security / control, efficiency, and service / service (PIECES) of Academic Information System. The evaluation results show that the performance of SIA is good (70,5%); SIA information is good (55.3%); The economic value of AIS is good (83.5%); SIA security is good (84.7%); SIA efficiency is good (51.8%); SIA service is good (77,6%).     Google Translate for Business:Translator ToolkitWebsite Translator